Chemical and Antimicrobial Studies of the Roots of Tephrosia villosa (L) Pers - Ganapaty, S.; Nyamathulla, S.; Srilakshmi, G.V.K.; Ravi Prasad, K.V.N.M. (Asian Journal of Chemistry, 2010)
Tephrosia villosa (L) Pers roots on chemical examination and sequential chromatography gave four compounds, stigmasterol, lupeol, rotenone and dehydrorotenone. Their structures were determined by various spectral techniques (1H NMR, IR, UV, MS) and elemental analysis. When the extracts were subjected to antimicrobial studies, a moderate activity was observed on tested bacteria and fungi.